IN-HOSPITAL MORTALITY IN ELDERLY (>75 YEARS) PATIENTS UNDERGOING PRIMARY PERCUTANEOUS CORONARY INTERVENTION (PCI) WITH ACUTE ST ELEVATION MYOCARDIAL INFARCTION AT AFIC-NIHD RAWALPINDI - Ghani, Imran; Rehman, Waheed Ur; Khan, Muhammad Qaiser; Aziz, Sohail; Siddiqa, Aysha; Khan, Qurban; Naseem, Shiasta; Farooq, Muhammad Asim (Pakistan Armed Forces Medical Journal, 2015)
Objective: To determine in hospital clinical outcome of primary PCI in elderly patients.Study Design: Descriptive cross-sectional study.Place and Duration of Study: This study was performed in Armed Force Institute of Cardiology from November 2011 to December 2014.Methods: This study consist of 1226, of which 69 were elder (>75 years) patients consecutive acute STEMI presenting to emergency department of hospital.Results: Angioplasty with stentig was done in 59 (81.1%) patients, whereas POBA only was done in 1 (1.4%) patients. Drug eluting stents (DES) were used in 15(21.7%) and bare metal stents were deployed in 41 (59.4%) patients. Temporary pace maker (TPM) was inserted in 5 (2.2%) patients. Intra aortic balloon pump was used in 3(4.3%) patients. The Median time from the onset of symptoms to arrival in the hospital was122.5 ± 142.57and median door to balloon time was 60 ± 22.88 min.Conclusion: Primary PCI for elderly patients presenting with acute ST segment elevation myocardial infarction is a safe and effective mode of revascularization with high success rate and low mortality.